Shifting Societal Attitudes: Examining the Effects of Perspective Taking on Attitudes toward and Derogation of the Poor. Issue 1 (2nd January 2019) - Wiese, Jessica Louise; Loomis, Colleen; Mitchell, Terry
ABSTRACT: People tend to hold negative attitudes about and derogate those in poverty to varying degrees, often relying on indivi-dualistic explanations of poverty that largely ignore systemic sources. This study (N = 208) examined a perspective-taking strategy that could be used to reduce distancing behaviors and negative attitudes toward the poor. Perspective takers distanced less and reported fewer negative attitudes than others. An additional finding was that men (n = 57) were more likely to derogate/distance than women, showed greater agreement with personal deficiency explanations for poverty, and reported stronger stereotypic attitudes toward people who are impoverished.